Figlie di immigrati e scrittrici: occhi adulti per volgersi al passato - Zannoni, Federico (Studi sulla Formazione/Open Journal of Education, 2012)
Writing, autobiography and narrative fiction are important means to reflect on themselves and to bring order to their inner self. This article reviews some excerpts from the work of some of the most interesting female voices, united from being daughters of immigrants, but above all women, sometimes mothers, able to reflect on their path, from childhood to their present life.